2012
DOI: 10.1103/physrevb.86.224423
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency and shot noises in CoFeB/MgO/CoFeB magnetic tunneling junctions

Abstract: The low-frequency and shot noises in spin-valve CoFeB/MgO/CoFeB magnetic tunneling junctions were studied at low temperature. The measured 1/f noise around the magnetic hysteresis loops of the free layer indicates that the main origin of the 1/f noise is the magnetic fluctuation, which is discussed in terms of a fluctuation-dissipation relation. Random telegraph noise (RTN) is observed to be symmetrically enhanced in the hysteresis loop with regard to the two magnetic configurations. We found that this enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 59 publications
3
33
1
Order By: Relevance
“…(2)(3), cannot implicitly be specified as different physical processes are potential origins. This includes intrinsic phenomena such as fluctuations in the magnetic texture 28,29,49 , the impact of defects and/or inhomogeneities in the magnetic layers or the tunnel barrier in particular due to the fabrication process 33 . Even external fluctuations of the driving dc current or the applied magnetic field can play a role.…”
Section: Results -Noise In Stvosmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)(3), cannot implicitly be specified as different physical processes are potential origins. This includes intrinsic phenomena such as fluctuations in the magnetic texture 28,29,49 , the impact of defects and/or inhomogeneities in the magnetic layers or the tunnel barrier in particular due to the fabrication process 33 . Even external fluctuations of the driving dc current or the applied magnetic field can play a role.…”
Section: Results -Noise In Stvosmentioning
confidence: 99%
“…Moreover, we apply up to ∼ 400 mV compared to a maximum bias voltage of ∼ 50 mV in Ref. 29 . Usually, α H decreases with higher applied voltages by up to one order of magnitude [54][55][56] due to new conductance channels arising in this range of biases (and the likewise decreasing TMR ratio) 54,56 .…”
Section: Governing Parameters and Relation To The Hooge Formalismmentioning
confidence: 99%
“…14,15 It has also been shown experimentally that the Fano factor in a single-barrier magnetic tunnel junction depends on magnetic configuration of the junction, and can be remarkably enhanced for the antiparallel alignment of the electrodes' magnetizations. [16][17][18][19][20] Even more possibilities have been found in double-barrier tunnel junctions with two ferromagnetic electrodes and one ferromagnetic central layer, 21,22 where one can distinguish four magnetic configurations corresponding to different alignments of the magnetic moments of all three magnetic layers. 23 It has also been shown that a simple model based on two well-separated spin channels for electronic transport cannot properly describe the experimental observations without taking into account spin-flip transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the magnetic noise of TMR sensors strongly correlates with derivative of a transfer curve ( dR / dH ) [5,10,11]. Therefore, we can define field sensitivity ( FS ) as a product of sensors bias current ( I b ) and the derivative, FS = I b dR / dH .…”
Section: Introductionmentioning
confidence: 99%